Cognitive component of auditory attention to natural speech events - Nhan Duc Thanh Nguyen; Kaare Mikkelsen; Preben Kidmose (Frontiers in Human Neuroscience)
The recent progress in auditory attention decoding (AAD) methods is based on algorithms that find a relation between the audio envelope and the neurophysiological response. The most popular approach is based on the reconstruction of the audio envelope from electroencephalogram (EEG) signals. These methods are primarily based on the exogenous response driven by the physical characteristics of the stimuli. In this study, we specifically investigate higher-level cognitive responses influenced by auditory attention to natural speech events. We designed a series of four experimental paradigms with increasing levels of realism: a word category oddball paradigm, a word category oddball paradigm with competing speakers, and competing speech streams with and without specific targets. We recorded EEG data using 32 scalp electrodes, as well as 12 in-ear electrodes (ear-EEG) from 24 participants. By using natural speech events and cognitive tasks, a cognitive event-related potential (ERP) component, which we believe is related to the well-known P3b component, was observed at parietal electrode sites with a latency of ~625 ms. Importantly, the component decreases in strength but is still significantly observable in increasingly realistic paradigms of multi-talker environments. We also show that the component can be observed in the in-ear EEG signals by using spatial filtering. We believe that the P3b-like cognitive component modulated by auditory attention can contribute to improving auditory attention decoding from electrophysiological recordings.